Análisis del artefacto indumentario chumbi de la mujer Salasak - Jerez Yansapanta, Jairo Paul (2023)
This project seeks to make visible the practical, communicative and technical-productive dimensions of the Salasaka women's chumbi, giving importance to the clothing artifact beyond its practical function in everyday life, it seeks to know why young adolescents have stopped using the chumbi compared to adult women who wear the accessory every day. The chumbi is an accessory with cultural richness that can be analyzed from the fashion point of view and as a methodology it has been found that the study belongs to a mixed approach, involving natives of the area, especially artisans and women. Thus, results have been obtained by means of semi-structured and triangulated interviews, as well as bibliographic cards, observation cards of the functions of the clothing artifact and surveys. As a result of the analysis of the practical, communicative and technical-productive functions, surveys and interviews, it was possible to identify a new practical function which is the increase of voice decibels when using the chumbi and it was verified that the chumbi is used by the younger population of the village, but with less frequency compared to the adult population. Likewise, a comparison was made between current and old chumbis, identifying changes in the use of fibers from natural to synthetic fibers, use of vibrant to opaque colors, form of production: vertical loom, callua or backstrap loom, among others.